Degradation of Lignosulfonate to Vanillic Acid Using Ferrate (Adv. Sustainable Syst. 4/2023). (19th April 2023) - Klein, Jana; Kupec, Robin; Stöckl, Markus; Waldvogel, Siegfried R.
Abstract : Vanilic Acid Article 2200431 by Markus Stöckl, Siegfried R. Waldvogel, and co‐workers demonstrates a new method how to obtain selectively vanillic acid, a flavouring agent and antioxidant, from side‐stream lignins by degradation using electrochemically generated ferrate as oxidizer. In times of climate changes the utilization of relevant bio‐based lignin as a renewable feedstock for fine chemicals is considered and will rival petroleum refining.